BEST PRACTICE OF CREDIT BANKING SYSTEM IN SCHOOL UNDER THE SECONDARY EDUCATION SERVICE AREA OFFICE PATHUMTHANI - Nithipattanakarn, Supakporn (Journal of Educational Review Faculty of Education in MCU, 2025)
This research aimed to 1) synthesize best practices of the credit bank system in school under the Secondary Education Service Area Office of Pathum Thani and 2) propose guidelines for best practices of the credit bank system in school under the Secondary Education Service Area Office of Pathum Thani. The key informants were divided into 2 groups as follows: Group 1: School administrators or deputy school directors in school under the Secondary Education Service Area Office Pathum Thani; 1 person per school, totaling 22 informants, using a semi-structured interview and Group 2: Teachers responsible for the credit bank system in school under the Secondary Education Service Area Office of Pathum Thani; 1 person per school, totaling 22 informants, using a focus group discussion and analyzed the data using descriptive analysis. The research results found that 1) Best practices of the credit bank system in school under the Secondary Education Service Area Office of Pathum Thani consisted of 5 aspects: Structure and Management, Criteria, Methods, Strategies and Results. 2) Guidelines for best practices of the credit bank system in school under the Secondary Education Service Area Office of Pathum Thani consisted of 8 aspects: 1) Connecting the credit bank system policy from the Ministry of Education to the Ministry of Higher Education, Science, Research and Innovation. 2) Defining the role of the agency responsible for controlling the credit transfer standards by considering the curriculum, course descriptions, learning management, measurement and evaluation, and monitoring the transfer results to create progress. 3) Creating documents, manuals, or guidelines for related agencies. 4) Organizing projects to enhance professional experience, students receive compensation according to their qualifications and create motivation for self-development. 5) Creating the distinctiveness of each area by setting the direction and designing the curriculum to focus on promoting specialized excellence. 6) Supporting the development of personnel to have specialized knowledge and skills through academic cooperation from government organizations, universities, and basic education institutions. 7) Reducing the cost of education for basic education students to encourage them to participate in the credit bank system more. 8) Developing learning through learning resources, both online and on-site, to continuously transfer credits into the credit bank system.